Features and characters for distributed system - Prof. Dr. Paul Mccullagh (Wasit Journal of Computer and Mathematics Science, 2022)
The introduction of microprocessors had created a number of product options that were just not there before. These clever processors have infiltrated and dispersed themselves across every aspect of our life, whether it be in the office (fax machines, pagers, laser printers, credit card readers), living rooms (televisions, air conditioners), or kitchens (food processors, microwave ovens). The usage of an operating system has many benefits as distributed applications get more complicated. The real-time demands of the majority of distributed systems need the usage of Real Time Operating Systems (RTOS) that can fulfill the needs of distributed systems. Real-time applications can be readily built and expanded thanks to RTOS. Through the division of the application code into different files, the use of RTOS streamlines the design process.
Keywords: OS, Real time, embedded system, distributed system